Development of Geometric Thought in High School Students, When They Learn the Concept of Homothecy [Desarrollo del Razonamiento Geométrico de Estudiantes de Enseñanza Media Cuando Abordan el Concepto de Homotecia] - Vanegas-Ortega, C (Comite Latinoamericano de Matematica Educativa, 2022)
The aim of this st udy is to characterize the development of levels of geometric thought in twelfth-grade chilean students, when they learn the concept of homothecy through a didactic sequence based on Van Hiele model. A qualitative methodology with a non-experiment al design was used in this st udy for describing how the concept of homothecy transforms, and thus the geometric thought. A pretest-posttest design was used to evaluate the acquisition of the Van Hiele levels to strengthen the analysis of the qualitative data. The main results show a complete acquisition of Level 0 for most students. In addition, the proposed activities allowed the development of Level 0, and enabled the development of the first levels of acquisition of Level 1. This achievement is enhanced thanks to the manipulative and virt ual resources used, the collaborative work among students and the sequencing of activities worked. © 2022, Comite Latinoamericano de Matematica Educativa. All rights reserved.